Kemampuan Perhatian Anak Autisme Pada Permainan Puzzle Di SLB Melati Rumbai Pekanbaru - Norlita, Wiwik; Isnaniar; Sari, Maya (Fakultas MIPA dan Kesehatan, Universitas Muhammadiyah Riau, 2021)
Autism or commonly called ASD Autistic Spectrum Disorder is a complex and highly varied disorder of development of brain function spectrum, usually these disorders include how to communicate, interact socially and imagine abilities. The concentration ability of autistic children is very low, this can be seen from the child's lack of ability to focus on when working on something, his attention is easily distracted, and often the child has difficulty in carrying out instructions. The purpose of this study is to find out the ability of attention of children with autism in puzzle games. This study used a descriptive method by retrieving using total sampling, with a total of 10 respondents. Based on the results of the study conducted on July 27 - August 7 2020 with the title of the study